Becoming Genealogical: Power and Diverse Economies. Issue 3 (2nd July 2020) - Sarmiento, Eric; Gabriel, Nate
Abstract : The community-economies approach eschews explanatory frameworks premised on structural analysis, arguing that such approaches prematurely foreclose the progressive potential of existing ethically oriented economic practices and enterprises. Several scholars have argued, however, that to activate the political potential and broader significance of noncapitalisms, it is necessary to trace their articulations with far-reaching political assemblages. To explore this point, this essay examines the genealogical orientation of some diverse- and community-economies research in conversation with the Nietzschean tradition of critical, constructive analysis and the notion of power as ontogenetic. It encourages a reinvigoration of the genealogical approach to diverse and community economies, emphasizing an assemblage-inflected understanding of genealogy as an ethos or mode of becoming rather than an analytic. This can enable diverse-economies research to confront power in all its forms without falling victim to the melancholic narrative of capitalist domination that such a focus too often engenders.